Distribution of Rugilus mixtus (Lohse, 1956) (Coleoptera: Staphylinidae: Paederinae) in Poland with comments of its morphology and ecological preferences - Sapieja, Mateusz; Ranocha, Magdalena; Melke, Andrzej (Zootaxa, 2022)
Rugilus mixtus (Lohse, 1956) is a rare species of Staphylinidae, found to exist only in a few European countries. In Poland, it was known from only three sites. Having analysed museum collections, we report 9 new locations. On the basis of the available literature and our observations of this species, we present its detailed ecological requirements, which, to date, are not fully recognized. The species is very likely to occur in humid biotopes, where the dead, rotting trees or stumps are essential elements and the vast majority of known sites are located in naturally important areas. Therefore, we suggest that Rugilus mixtus may be used as an indicator species in studies aimed to evaluate the naturalness of forest. In order to facilitate the correct identification of this species, we have used illustrations and photographs of their aedeagi to create a key for four similar species of the genus Rugilus occurring in central Europe.